(untitled) (International Journal of Innovative Technologies in Economy, 2022)
Social-economic development of mountain regions mostly depends on maximum usage of existing resources, which constitutes of urgent issues of contemporaneity. In line with all this the special significance is granted to application of touristic and recreational resources in Georgia, which constitutes the priority trend for sustainable economic development of mountain regions. The work has studied the basic touristic and recreational properties of Makhuntseti Waterfall of Mountainous Adjaria and its place in tourism business development in the region. There is grounded the priority of natural-geographic and social-economic conditions necessary to establish Makhuntseti as a resort. Besides, under complex, unstable natural conditions and in terms of limited resources - the supremacy of tourism among business areas is determined and its further perspectives are established.